Pigment identification and antioxidant properties of red dragon fruit (Hylocereus polyrhizus) - Rebecca, O.P.S.; Boyce, Amru Nasrulhaq; Chandran, S. (Academic Journals, 2010)
The aim of this study was to identify pigments present in the red dragon fruit (Hylocereus polyrhizus) and to further investigate the antioxidant properties in this fruit. Pigment was identified using the High Performance Liquid Chromatography (HPLC) and results confirmed the presence of betanin in sample at a retention time of 11.5 min which corresponded to the retention time of the betanin standard used. In the antioxidant properties determination, there were 86.10 mg of total polyphenolic compound in 0.50 g of dried dragon fruit extract using the total polyphenol assay which expresses gallic acid as equivalent. The reducing power assay further confirmed the antioxidant activity present in dragon fruit where the reducing capability increased from 0.18 to 2.37 with the increase of dry weight sample from 0.03 to 0.5 g. The Vanillin-HCl assay which measures the amount of condensed tannin showed that the dried dragon fruit sample had an equivalent of 2.30 mg catechin/g. The DPPH center dot radical scavenging activity determination showed that the effective concentration (EC(50)) for dragon fruit was 2.90 mM vitamin C equivalents/g dried extract.